2017
DOI: 10.1002/ace.20218
|View full text |Cite
|
Sign up to set email alerts
|

Critical Culture: Environmental Adult Education in Public Museums

Abstract: This chapter explores how museums, as educational and cultural institutions, can become agents of socioecological transformation. The ideas of critical museum studies and environmental adult education are reviewed, and three examples of environmental adult education in museums are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In 2018, a large fraction of adults (61%) reported visiting an ILI in the 12 months prior to being surveyed (NSB, 2020), making ILI a significant resource for adult STEM learning. Adult participation and STEM-related learning have been explored in museum programs (Bell & Clover, 2017), science centers (Gutwill, 2018), and zoos and aquaria (Gupta et al, 2019); yet, extent of ILIs support for STEM integration with contemporary SSI is unclear. In a review of how ILIs position STEM knowledge related to SSI, Morrissey et al (2022) found ILIs primarily helped visitors gain knowledge and recognize evidence (versus discussing solutions) and often examined issues (e.g., race as a social construct) in isolation from complex societal structures (e.g., nuances of racism in America).…”
Section: Adult Stem Educationmentioning
confidence: 99%
“…In 2018, a large fraction of adults (61%) reported visiting an ILI in the 12 months prior to being surveyed (NSB, 2020), making ILI a significant resource for adult STEM learning. Adult participation and STEM-related learning have been explored in museum programs (Bell & Clover, 2017), science centers (Gutwill, 2018), and zoos and aquaria (Gupta et al, 2019); yet, extent of ILIs support for STEM integration with contemporary SSI is unclear. In a review of how ILIs position STEM knowledge related to SSI, Morrissey et al (2022) found ILIs primarily helped visitors gain knowledge and recognize evidence (versus discussing solutions) and often examined issues (e.g., race as a social construct) in isolation from complex societal structures (e.g., nuances of racism in America).…”
Section: Adult Stem Educationmentioning
confidence: 99%
“…Our research regarding music and social learning also contributes to broader discussions regarding art-based and aesthetic adult education. This research has pointed to the power of art to facilitate education on social issues, including ecojustice, women's rights, and public health (Bell & Clover, 2017;Clover, 2015Clover, , 2018Collins, 2012). Additionally, Karafillidis (2012) argued that visual and musical arts could reinforce one another to enhance a learner's artistic appreciation.…”
Section: Facilitating Change Using Music and Visual Artmentioning
confidence: 99%
“…Moreover, this separation or segregation of artefacts (things made by humans) from "specimens" from the natural world is based in what feminist's call hierarchical value judgments (e.g. Bergsdottir, 2016;Clover & Sanford, 2016;Machin, 2008). In other words, segregating is not neutral or objective but an act of privileging the story of humanity -and particularly some humanity -over the natural world which plays the role of mise-en-scene, the backdrop to human activity.…”
Section: Museums Ideological and Epistemological Complicitiesmentioning
confidence: 99%
“…The Kitimat museum is located at the terminus of a most controversial pipeline project to carry thousands of barrels of "diluted bitumen per day from the oil sands of Alberta across Rocky and Coast mountain ranges, salmon spawning rivers and Indigenous territories" and onto "supertankers" (large tanker ships) to be shipped aboard for refining through extremely narrow and hazardous (shoals, eddies, storms) passages (Bell & Clover, 2017, p. 23). The Kitimat Museum staff called upon local citizens and artists to help them to create an exhibition that explored the issue of energy production creatively and from a variety of other angles (Bell & Clover, 2017). The museum staff also gathered questions from the community about energy production and social and ecological issues, which they grouped into themes such as economy, activism, risk, and consultation and presented to officials in both government and the petroleum/pipeline industry for their responses.…”
Section: Bridging Community and Industrymentioning
confidence: 99%
See 1 more Smart Citation